The Role of Corporate Finance in Maximizing Shareholder Wealth and Driving Sustainable Growth - Ermawati, Yana (Advances in Management & Financial Reporting, 2024)
Purpose: This research comprehensively explores the multifaceted dynamics of corporate finance and its critical role in maximizing shareholder wealth and driving sustainable growth in organizations. Research Design and Methodology: This study uses qualitative research to synthesize insights from multiple disciplines, including traditional finance theory, empirical evidence, behavioral finance insights, and regulatory analysis. Findings and Discussion: The results highlight the importance of capital structure decisions, dividend policy choices, and effective corporate governance mechanisms in influencing shareholder value creation and firm performance. In addition, integrating sustainable practices, particularly environmental, social, and governance (ESG) factors, is emerging as an essential trend shaping corporate finance practices. These findings confirm the need for adaptive financial strategies and strong management, especially in emerging markets. Implications: The findings demonstrate the importance of adaptive financial strategies and strong governance in creating shareholder value and promoting sustainable growth. They may inform regulatory reforms to improve corporate finance practices' transparency, accountability, and market integrity.